2014
DOI: 10.1080/14763141.2014.982697
|View full text |Cite
|
Sign up to set email alerts
|

Changing the stability conditions in a back squat: the effect on maximum load lifted and erector spinae muscle activity

Abstract: The aim of this study was to identify how changes in the stability conditions of a back squat affect maximal loads lifted and erector spinae muscle activity. Fourteen male participants performed a Smith Machine (SM) squat, the most stable condition, a barbell back (BB) squat, and Tendo-destabilizing bar (TBB) squat, the least stable condition. A one repetition max (1-RM) was established in each squat condition, before electromyography (EMG) activity of the erector spinae was measured at 85% of 1-RM. Results in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 31 publications
1
16
1
Order By: Relevance
“…Mean 1RM for HS was 29 kg (18%) greater than BS, significantly more than the 11% difference between Smith Machine and BS 1RM previously reported 14 . As such, we demonstrated that absolute test loads at 65, 75, 85 and 95% SM were higher in HS than BS.…”
Section: A C C E P T E Dcontrasting
confidence: 51%
See 4 more Smart Citations
“…Mean 1RM for HS was 29 kg (18%) greater than BS, significantly more than the 11% difference between Smith Machine and BS 1RM previously reported 14 . As such, we demonstrated that absolute test loads at 65, 75, 85 and 95% SM were higher in HS than BS.…”
Section: A C C E P T E Dcontrasting
confidence: 51%
“…Research investigating the BS [11][12][13][14][15] , front squat 12,13,16 , and overhead squat 15 have confirmed that the loaded, free barbell squat is an effective method of activating the stabilizing muscles of the trunk. There is also evidence that in BS magnitude of activation across the majority of muscle sites is sensitive to the external load 1,11,17,18 .…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations